Allicin Alleviates Reticuloendotheliosis Virus-Induced Immunosuppression via ERK/Mitogen-Activated Protein Kinase Pathway in Specific Pathogen-Free Chickens - Wang, Liyuan; Jiao, Hongchao; Zhao, Jingpeng; Wang, Xiaojuan; Sun, Shuhong; Lin, Hai (Frontiers in Immunology, 2017)
Reticuloendotheliosis virus (REV), a gammaretrovirus in the Retroviridae family, causes an immunosuppressive, oncogenic and runting-stunting syndrome in multiple avian hosts. Allicin, the main effective component of garlic, has a broad spectrum of pharmacological properties. The hypothesis that allicin could relieve REV-induced immunosuppression was investigated in vivo and in vitro in the present study. The results showed that dietary allicin supplementation ameliorated REV-induced dysplasia and immune dysfunction in REV-infected chickens. Compared with the control groups, REV infection promoted the expression of inflammatory cytokines including interleukin-1β (IL-1β), IL-6, IL-10, interferon gamma (IFN-γ) and tumor necrosis factor-α(TNF-α), whereas, allicin reversed these changes induced by REV infection. The decreased levels of IFN-α, IFN-β and IL-2 were observed in REV-infected chickens, which were significantly improved by allicin. Allicin suppressed the REV-induced high expression of Toll-like receptors (TLRs) as well as melanoma differentiation-associated gene 5 (MDA5), and the activation of mitogen-activated protein kinase (MAPK) and the nuclear factor kappa B (NF-κB) p65. REV stimulated the phosphorylation of JNK, ERK and p38, the downstream key signaling molecules of MAPK pathway, while allicin retarded the augmented phosphorylation level induced by REV infection. The decreased phosphorylation level of ERK was associated with REV replication, suggesting that ERK signaling is involved in REV replication and allicin can alleviate the REV-induced immune dysfunction by inhibited the activation of ERK. In addition, REV infection induced oxidative damage in thymus and spleen, whereas allicin treatment significantly decreased the oxidative stress induced by REV infection, suggesting the antioxidant effect of allicin should be at least partially responsible for the harmful effect of REV infection. In conclusion, the findings suggest that allicin alleviates the inflammation and oxidative damage caused by REV infection and exerts the potential anti-REV effect by blocking ERK/MAPK pathway.